Man and Machine in the Image of God: Ḥaim Zelig Slonimski as a Herald of Technological Innovation in the Jewish Enlightenment (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2025)
In this article, I examine the work and thought of Ḥaim Zelig Slonimski, a key figure in the Jewish Enlightenment (Haskalah) movement in nineteenth-century Eastern Europe. I focus on his engagement with technological innovation, a topic that has not been sufficiently analyzed in the scholarly literature. Unlike the common perception of Slonimski as a popularizer of science, I argue that he attributed great importance to technological innovation as a driver of society’s transition into the Age of Enlightenment. A systematic analysis of his writings on the subject sheds light on his views regarding telephone and telegraph lines, electrical networks, railways, and steam engines, not merely as applications of science but as powerful mechanisms in their own right, paving the way for individuals and society toward the Enlightenment. Moreover, I make clear the synthesis Slonimski created between technological innovation and the Jewish religious worldview. In his conception, new technological inventions embodied a divine spark inherent in the human intellect, offering a dual pathway: both the advancement of knowledge and science and the strengthening of faith. Based on these findings, I propose a new interpretation of Slonimski’s role in the Haskalah – not as a mediator of scientific knowledge, but rather as a popularizer of technological innovation. This term more accurately reflects his techno-Enlightenment worldview.
Keywords: Haim Zelig Slonimski; Haskalah movement; Ha-Tzfira newspaper; popularizers of science; technological innovation